ANALISIS PELAKSANAAN TUGAS DINAS PEMADAM KEBAKARAN KOTA PEKANBARU PADA TAHUN 2008-2012 - Yudhi Kuswandi; Hery Suryadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study entitled " Analysis of the Implementation Task Pekanbaru CityFire Department In The Year 2008-2012 " . It is the underlying catastrophic firesthat often occur in the community . Therefore, prevention efforts should be madeand involve all members of the community , one of the ways is through thedissemination to the public about the fire because one of the causes of fire due tolack of public awareness about the dangers of fire and the lack of expertise in thefield of fire .The problems of this research is how the Implementation Task PekanbaruCity Fire Department and what are the constraints faced by the Fire Department .This study aims to determine how the execution of tasks Pekanbaru City FireDepartment and to find out what are the constraints faced Pekanbaru City FireDepartment.With the scope of research on the execution of tasks of the FireDepartment , this study tries to explain the results of the implementation of thetasks of the Fire Department . In this study , the data collection is done by takingthe existing data in the field as well as interviews conducted by authorized partiesFrom the results of this research is that the execution of tasks Pekanbaru City FireDepartment is still not running as well as possible , it can be seen from the manyconstraints faced by officers and employees in the Fire Department as well as thelack of outreach to the community and lack of infrastructure tools in PekanbaruCity Fire Department . This of course can not fully achieve the goals that havebeen set up to help people in case of fire disasterKeywords : Analysis , Implementation Task , Pekanbaru City Fire Department